IMPLEMENTATION METHOD - LUPU, Cătălin (Universitatii Stefan cel Mare din Suceava, 2018)
In this article presents applications of “Divide et impera” method using object -oriented programming in C #.Main advantage of using the "divide et impera" cost in that it allows software to reduce the complexity of the problem,sub-problems that were being decomposed and simpler data sharing in smaller groups of data (eg sub -algorithmQuickSort). Object-oriented programming means programs with new types that integrates both data and methodsassociated with the creation, processing and destruction of such data. To gain advantages through abstractionprogramming (the program is no longer a succession of processing, but a set of objects to life, have differentproperties, are capable of specific action s and interact in the program). Spoke on instantiation new techniques,derivation and polimorfismul object types.